Performance of a Balanced Portfolio With Active Covered-Call Strategies - El-Hassan, N.; Hall, A.; Tulunay, I. (Journal of Applied Business and Economics, 2022)
This study investigates the performance of local and global investments with and without covered call option strategies over the period from January 2000 to December 2015. The Covered Call Strategy (CCS) is a common return enhancing strategy used in portfolio management. The strategy consists of simultaneously holding a long position in an asset and writing call options on that asset. The local investment are on the top twenty stocks from Australian market while the global investment is an international balanced portfolio. For covered call strategies, market option data from Australian Stock Exchange is used. The results show that under some constraints, using covered call strategies in general improves the risk-adjusted returns.